PENGARUH PROMOSI KESEHATAN TERHADAP CARA MENGGOSOK GIGI PADA ANAK BERKEBUTUHAN KHUSUS DI SMART AURICA SCHOOL MEDAN - Efrida Batubara (Program Studi Ilmu Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Indonesia Timur, 2020)
Teach and promote a variety of clean and healthy living habits such as how to brush teeth to children with special needs is indeed different. In addition to habituation, children also need to be given concrete examples in the learning process. Various kinds of tools or media that can be used to promote health in children with special needs, one of which is audiovisual media. The purpose of this study was to analyze the effect of health promotion on how to brush teeth in children with special needs. The type of research is quasi experimental with group pretest posttest design. The study population was 60 people and all of them used as samples (exhaustive sampling or total sampling). Data analysis was performed univariately and continued with bivariate analysis using paired samples t test. The results showed that before being given audiovisual media counseling (pretest) most children brushed their teeth in the sufficient category of 66.7%, while the good ones were only 6.7%. After being counseled the majority of tooth brushing was already good at 56.7%, with less than 3.3% remaining. There is a significant influence of health promotion using audiovisual on the way to brush teeth on children with special needs at Smart Aurica School Medan in 2019, p = 0,000 <0.05. An increase in the score of ways to brush the teeth of children after getting health promotion through audiovisual with an average score of 6.10 pretest and posttest to 7.82. The teachers and management at Smart Aurica School Medan can implement tooth brushing activities and use audiovisual media as an alternative learning media so that children with special needs do not feel bored or bored when participating in learning.